Students’ Perceptions of the impacts of Short Diplomatic Course 2023: An Interpretive Phenomenology on Diplomatic Academic Experience, Personal Development and Global Perspective - Juliana, Juliana (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Komputer Indonesia, 2024)
Purpose of this research was to examine students’ perception of international relation on the impact of short diplomatic course program 2023 with the topic